Comparison of PKRP and TUVP in the treatment of high-risk BPH and analysis of postoperative influencing factors - Song, Yao; Pang, Songqiang; Luo, Gongtang; Li, Sen; He, Yaqiang; Yang, Jinqiang (Frontiers in Surgery, 2022)
Objective This study aims to compare the efficacy of plasma kinetic loop resection of the prostate (PKRP) and transurethral vaporization of the prostate (TUVP) for the treatment of high-risk benign prostatic hyperplasia (BPH), and analyze the influence of the related factors on the operation of BPH. Methods A total of 108 high-risk BPH patients diagnosed in our hospital from March 2018 to September 2021 were selected and randomly divided into an observation group and a control group, with 54 cases in each group. The control group was treated with TUVP, and the observation group was treated with PKRP. The international prostate symptom score (IPSS), quality of life (QOL) index, maximum urine flow rate (Qmax), and residual urine volume (RU) were observed before and after treatment. The general information such as age, educational level, residence, and residence status of the patient, as well as clinical information such as surgical method, nocturia frequency, preoperative IPSS score, RU, medical history, and prostate texture, were also recorded. All patients were followed up for 1 month, and complications were recorded. Results The IPSS score, QOL score, and RU of patients in the two groups were lower after treatment than those before treatment, and the Qmax was higher than that before treatment (P < 0.05). The IPSS score, QOL score, and RU of the observation group were lower than those of the control group, and the Qmax was higher than that of the control group (P < 0.05). The incidence of postoperative complications in the observation group was lower than in the control group (P < 0.05). Univariate analysis showed that the patient's age, surgical method, nocturia frequency, preoperative IPSS score, RU, medical history, and prostatic texture all could affect the postoperative condition of patients with BPH (P < 0.05). Multivariate logistic analysis showed that the patient's age, surgical method, nocturia frequency, preoperative IPSS score, RU, and medical history were the independent influencing factors of the postoperative condition of patients with BPH (P < 0.05). Conclusion PKRP in the treatment of high-risk BPH patients can effectively reduce the IPSS score, QOL score, and RU and significantly increase Qmax, with fewer complications and a good prognosis. Patients’ postoperative recovery was related to their age, surgical method, nocturia frequency, preoperative IPSS score, RU, and medical history. Therefore, choosing PKRP to treat high-risk BPH patients can effectively improve the postoperative urethral functional recovery of patients and reduce the occurrence of complications.